2005
DOI: 10.1142/s0218810405002425
|View full text |Cite
|
Sign up to set email alerts
|

Is Symptomatology Useful in Distinguishing Between Carpal Tunnel Syndrome and Cervical Spondylosis?

Abstract: Hand paraesthesia is a common symptom found in patients either with carpal tunnel syndrome or cervical spondylosis. To differentiate between the two conditions, it is important to identify additional diagnostic symptoms. Ninety-two patients with operated carpal tunnel syndrome and 138 patients with spinal surgery for cervical spondylosis were reviewed. After exclusion of cases co-morbid with both cervical spondylosis and carpal tunnel syndrome or other neurological disorders, 44 patients with carpal tunnel syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
1
13
0
1
Order By: Relevance
“…4 The recognition of ulnar nerve compression of cyclists in Guyon's canal has been commonly described in the literature for decades. 1,[5][6][7][8][9][10][11] A noteworthy predisposing factor for ulnar nerve neuropathy is mechanical nerve perturbation in the thoracic outlet, including thoracic outlet syndrome, which is most often caused by compression or tension loading of the brachial plexus as it passes through the thoracic outlet. 12,13 This mechanical irritation produces a double crush phenomenon, in which the ulnar nerve is susceptible to altered axonal transport at the cubital tunnel and/or Guyon's canal when the compression and/or tension of the C8-T1 nerve roots compromise the nerve's ability to withstand additional pressure.…”
Section: Introductionmentioning
confidence: 99%
“…4 The recognition of ulnar nerve compression of cyclists in Guyon's canal has been commonly described in the literature for decades. 1,[5][6][7][8][9][10][11] A noteworthy predisposing factor for ulnar nerve neuropathy is mechanical nerve perturbation in the thoracic outlet, including thoracic outlet syndrome, which is most often caused by compression or tension loading of the brachial plexus as it passes through the thoracic outlet. 12,13 This mechanical irritation produces a double crush phenomenon, in which the ulnar nerve is susceptible to altered axonal transport at the cubital tunnel and/or Guyon's canal when the compression and/or tension of the C8-T1 nerve roots compromise the nerve's ability to withstand additional pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Zanette et al 35 reported that 45% of patients with CTS exhibited proximal pain, (ie, pain throughout the upper extremity). Chow et al 6 found that neck pain was present in 14% of patients with CTS. Finally, Reading et al 27 determined that symptoms involving the sensory distribution of the median nerve can be related to neck disorders.…”
mentioning
confidence: 99%
“…A median nerve distal sensory latency greater than 3.60 milliseconds and a median nerve distal motor latency greater than 4.20 milliseconds were considered as abnormal. 15 Patients were excluded if they exhibited any of the following: (1) extreme or severe CTS, (2) any sensory or motor deficit for either the ulnar or radial nerve, (3) age older than 65 years, (4) a history of wrist, upper extremity, or cervical spine trauma (whiplash), (5) previous wrist, upper extremity, or cervical surgery, (6) previously received a steroid injection, (7) multiple diagnoses for the upper extremity, (8) a history suggesting systemic disease causing CTS (eg, diabetes mellitus, thyroid disease), (9) pregnancy, (10) a concomitant medical condition (eg, rheumatoid arthritis, fibromyalgia), or (11) involved with or seeking litigation at the time of the study.…”
mentioning
confidence: 99%
“…For practical purposes, women with mild and moderate CTS were considered in the same group. 9 Differences in clinical pain parameters and function (BCTQ) among the 3 groups with CTS were compared with the nonparametric Kruskal-Wallis test. For the main objective of the study, a 2-by-4 mixed-model analysis of variance (ANOVA) was used to evaluate the differences in cervical range of motion for lateral flexion and rotation motion, with side (the affected side in participants with CTS and the dominant/nondominant in controls) as the within-subject factor and group (minimal, mild/moderate, severe, and controls) as the between-subject factor.…”
Section: Discussionmentioning
confidence: 99%
“…19 Some authors have found that individuals with CTS usually experience pain symptoms in the neck and the shoulder regions. 9, 27 Hurst et al 13 found that the presence of arthritis in the neck may result in compression of the cervical nerve roots in people with CTS, whereas Pierre-Jerome and Bekkelund 18 found that individuals with CTS, compared to a control group, exhibited higher incidence of narrowing of the cervical foramen. These studies suggest that compromised neural foramen could potentially lead to nerve root compression, predisposing patients to develop CTS or aggravating existing symptoms of CTS through a secondary site of compression.…”
mentioning
confidence: 99%